The Influence of Student Affairs Organizations on Students’ Learning Achievement of the FEB UTP Surakarta Management Study Program - Habibatul Adlyah Putri; Joko Tulus; Fikto Ardian Pramono; Zandra Dwanita Widodo (Asian Journal of Applied Business and Management, 2023)
This research aims to understand how student organizations influence student learning achievement in Management study program students at the Faculty of Economics and Business (FEB) Tunas Pembangunan University (UTP) Surakarta. The sample taken in this research was 20 students. This data collection technique used a non-probability sampling technique with a voluntary respondent sampling method. Based on the results of the regression test analysis, it shows that with every existence of a Student Affairs organization there will be a decrease in student achievement in the UTP Surakarta management study program by -0.019. Based on the test value of the coefficient of determination (R square) of 0.000, it means that it can be concluded that 0% of student learning outcomes are not determined by Student Organizations, meaning that only the remaining 21.9% are influenced by Student Organizations.